2020
DOI: 10.3389/fevo.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Growing Population of Eastern Migratory Monarch Butterflies Is Currently Insufficient

Abstract: The eastern migratory population of monarch butterflies has experienced a multidecadal decline, but a recent increase in abundance (to 6.05 ha in winter 2018) has led some observers to question whether the population has reversed its long-standing decline and embarked on a trajectory of increasing abundance. We examined this possibility through changepoint analyses, assessing whether a change in trajectory existed over a 25-year times series. We found evidence of a change in trajectory in 2014, but insufficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The first addition was to evaluate the assumption of a constant population change rate and to report TYC values derived from models that accommodate variable change rates if the assumption was not supported. Previous work (Thogmartin et al, 2020) and this analysis both demonstrate that a constant rate assumption is not appropriate for this time series. increased from nearly 0% to 90% (Thogmartin, Wiederholt, et al, 2017).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The first addition was to evaluate the assumption of a constant population change rate and to report TYC values derived from models that accommodate variable change rates if the assumption was not supported. Previous work (Thogmartin et al, 2020) and this analysis both demonstrate that a constant rate assumption is not appropriate for this time series. increased from nearly 0% to 90% (Thogmartin, Wiederholt, et al, 2017).…”
Section: Discussionmentioning
confidence: 74%
“…Previous work (Thogmartin et al, 2020) and this analysis both demonstrate that a constant rate assumption is not appropriate for this time series. increased from nearly 0% to 90% (Thogmartin, Wiederholt, et al, 2017). As herbicide use and habitat loss stabilised, Thogmartin, Wiederholt, et al (2017) concluded that further herbicide-associated declines in monarchs were not expected, and that monarchs would likely level off at a new stationary population size.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations